Influence of intra-abomasal administration of L-DOPA on circulating catecholamines and feed intake in cattle - Valente, Eriton E. L.; Klotz, James L.; Egert-McLean, Amanda M.; Costa, Gustavo W.; May, John B.; Harmon, David L. (Frontiers in Animal Science, 2023)
Dopamine has multiple physiological functions including feed intake control in which it can act as an anorectic or orexigenic agent. This study had the objective to evaluate intra-abomasal administration of L-DOPA from a plant extract on circulating catecholamines, energy metabolism and feed intake in cattle. Eight Holstein steers (340 ± 20 kg) fitted with ruminal cannula were used in a replicated 4 x 4 Latin Square design experiment. Intra-abomasal infusion of L-DOPA at 0, 0.5, 1 and 2 mg/kg BW was carried out for seven days and blood samples were collected at 0, 30, 60, 120, 240 and 480 min from L-DOPA infusion on day 7. The area under the curve (AUC) of plasma L-DOPA and free dopamine increased quadratically with the administration of L-DOPA. However, the AUC of plasma total dopamine had a positive linear response with the increase of L-DOPA. Conversely, the serum 5-HTP, plasma serotonin, serum serotonin, serum tyrosine, plasma glucose and plasma free fatty acids were not affected by the intra-abomasal infusion of L-DOPA. The circulating concentration of the epinephrine, norepinephrine, serotonin, glucose and free fatty acids did not change with L-DOPA infusion. It can be concluded that intra-abomasal L-DOPA administration produced a strong increase in circulating dopamine with no change in energy metabolites and feed intake in cattle.